2020
DOI: 10.46367/jas.v4i2.255
|View full text |Cite
|
Sign up to set email alerts
|

Peran Dan Kompetensi Auditor Syariah Dalam Menunjang Kinerja Perbankan Syariah

Abstract: The increase in the growth of Islamic banking needs to be supported by the performance of sharia auditors. This study aims to discuss the role and competence of Islamic auditors in supporting the performance of Islamic banking. This type of research uses qualitative methods with a descriptive approach using literature study data. The results of this study indicate that the competencies that must be possessed by sharia auditors include knowledge of Islamic law, fiqh muamalah, skills in accounting and auditing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(35 reference statements)
0
4
0
6
Order By: Relevance
“…Then the research conducted by Khalid, A.A., Haron, H. and Masron (2018) concluded that competence is the only independent variable affecting the quality of sharia internal Audits in Islamic financial institutions. However, in the research conducted by Jusri & Maulidha (2020), the study's results indicate that the competence of auditors does not impact the practice of shariah auditing.…”
Section: Results and Discussion Auditor Competencementioning
confidence: 77%
See 1 more Smart Citation
“…Then the research conducted by Khalid, A.A., Haron, H. and Masron (2018) concluded that competence is the only independent variable affecting the quality of sharia internal Audits in Islamic financial institutions. However, in the research conducted by Jusri & Maulidha (2020), the study's results indicate that the competence of auditors does not impact the practice of shariah auditing.…”
Section: Results and Discussion Auditor Competencementioning
confidence: 77%
“…General knowledge related to the sciences obtained during formal education includes: Islamic banking, fiqh muamalah, Auditing, conventional banking, risk management, mathematics, business accounting, related laws, internal control, and risk mapping. While specific knowledge is the knowledge gained from additional training (Jusri & Maulidha, 2020). Based on the Internal Audit Professional Standard (1210.2), it is stated that in detecting indications of fraud, the knowledge possessed by internal auditors must be sufficient (Ratri & Bernawati, 2020).…”
Section: Auditor Knowledgementioning
confidence: 99%
“…Kompetensi dari auditor tersebut dapat menjadi kunci untuk menunjang kinerja Perbankan Syariah (Elfadhli et al, 2021;Jusri & Maulidha, 2020) serta efektivitas dari keberadaan auditor internal syariah di BPRS itu sendiri.…”
Section: Pendahuluanunclassified
“…Jika mencermati dari aspek kompetensi auditor, maka akan terdapat banyak sekali pengembangan dan perdebatan maupun kajian tentang hal tersebut. Namun yang perlu diketahui bahwa kompetensi auditor khusus syariah harus mencakup pengetahuannya tentang hukum Islam, fiqh muamalah, keterampilan di bidang akuntansi dan audit, serta karakteristik khusus sebagai auditor syariah (Jusri & Maulidha, 2020).…”
Section: Telaah Teoriunclassified
“…The role and competence of sharia auditors are maximizing the role and competence of sharia auditors to support and support performance in sharia banking. Thus, the role of sharia auditors, among others, as stated in the opinion (Jusri and Maulidha 2020) can exist in the realm of independent auditors, internal auditors, and also as sharia supervisory boards. Sharia compliance that exists in Islamic financial institutions is part of the role of the sharia auditor itself.…”
Section: Literature Reviewmentioning
confidence: 99%